Preparation and Quality Evaluation of “Timur Raksi”, an Indigenous Alcoholic Beverage of Rolpa, Nepal - Subedi, Kusum; Dhungel, Abhitosh (Journal of Food Science and Technology Nepal, 2024)
The Timur raksi is an indigenous distilled alcoholic beverage made in Rolpa, Nepal. The study aimed to formulate timur raksi in the lab using various timur ratios, analyze chemical changes (pH, TSS, reducing sugar) during fermentation, evaluate chemical and sensory attributes of the final product, and assess yield and cost. The survey collected sample R1 from Rolpa. Rice and manapu were used for the first fermentation, while mana and jaggery were used for the second. Raksi samples R2, R3, and R4 were prepared using 50g, 75g, and 100g of timur, respectively. The proximate analyses of rice, jaggery, and timur were done. Reducing sugar, pH, and TSS were measured every 7 days throughout fermentation. The ethanol concentration of five distillate cycles (1 pani, 2 pani, 3 pani, 4 pani, and 5 pani) was determined. Total acidity was analyzed for final product. Propyl alcohol, ethyl acetate, isobutanol, acetal, fusel oil, acytol, linalol, ethyl palmitate, and D-limonene were the components discovered in samples R1, R2, R3, and R4 by GC-MS. The total yields of samples R2, R3, and R4 were 88.49%, 88%, and 87.53%, respectively. It can be concluded that on the basis of sensory evaluation, R3 was found to be the most preferable. The cost of the best product (R3) obtained was reasonably priced compared to market whiskey.